The Efforts of Madrasah Principals and Islamic Religious Education Teachers in Minimizing Bullying in State Islamic Junior High Schools of Padangsidimpuan City - Azwar Harahap; Zulhammi Zulhammi; Muhammad Roihan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
Bullying is a serious issue that frequently occurs in educational environments, including State Islamic Junior High Schools in Padangsidimpuan City specially verbal, phsyc, social and cyber (cyberbullying). This study aims to describe the efforts of madrasah principals and Islamic Religious Education (PAI) teachers in minimizing bullying behavior within the school environment. The method used in this study was a qualitative approach with data collection techniques conducted through observation, interviews, and documentation. The study population and sample consisted of 2 principals of State Islamic Junior High Schools (Madrasah Tsanawiyah Negeri) in Padangsidimpuan City, 22 Islamic Religious Education teachers of State Islamic Junior High Schools in Padangsidimpuan City, and 60 students of State Islamic Junior High Schools in Padangsidimpuan City. The analysis employed data reduction, data presentation, and conclusion drawing techniques, which were obtained through discussions with supervisors and validators that experts in their respective fields of expertise. The findings reveal that madrasah principals play an active role in formulating anti-bullying policies, fostering a religious school culture, and conducting intensive supervision. Meanwhile, PAI teachers contribute by instilling noble moral values, developing students’ character, and applying persuasive as well as preventive approaches in the learning process. The synergy between madrasah principals and PAI teachers has proven effective in reducing bullying cases and creating a safe and conducive learning environment. In line with the objectives outlined at the beginning of this study, bullying behavior can be minimized within the madrasah environment, particularly at State Islamic Junior High Schools in Padangsidimpuan City. It is hoped that this research will provide benefits for madrasahs and related parties, as well as serve as a valuable reference for future researchers.